Signal transducer and activator of transcription-3 is required in hypothalamic agouti-related protein/neuropeptide Y neurons for normal energy homeostasis - Gong, Lijie (2008)
Signal transducer and activator of transcription (Stat)-3 signals mediate many of the metabolic effects of the fat cell-derived hormone, leptin. In mice, brain-specific depletion of either the long form of the leptin receptor (Lepr) or Stat3 results in comparable obese phenotypes as does replacement of Lepr with an altered leptin receptor locus that codes for a Lepr unable to interact with Stat3. Among the multiple brain regions containing leptin-sensitive Stat3 sites, cells expressing feeding-related neuropeptides in the arcuate nucleus of the hypothalamus have received much of the focus. To determine the contribution to energy homeostasis of Stat3 expressed in agouti-related protein (Agrp)/neuropeptide Y (Npy) arcuate neurons, Stat3 was deleted specifically from these cells, and several metabolic indices were measured. It was found that deletion of Stat3 from Agrp/Npy neurons resulted in modest weight gain that was accounted for by increased adiposity. Agrp/Stat3-deficient mice also showed hyperleptinemia, and high-fat diet-induced hyperinsulinemia. Stat3 deletion in Agrp/Npy neurons also resulted in altered hypothalamic gene expression indicated by increased Npy mRNA and decreased induction of suppressor of cytokine signaling-3 in response to leptin. Agrp mRNA levels in the fed or fasted state were unaffected. Behaviorally, mice without Stat3 in Agrp/Npy neurons were mildly hyperphagic and hyporesponsive to leptin. We conclude that Stat3 in Agrp/Npy neurons is required for normal energy homeostasis, but Stat3 signaling in other brain areas also contributes to the regulation of energy homeostasis.